Use of non-specific immunoglobulins in Catalonia in three third-level hospitals: a descriptive analysis of a hospital-prescribed medication registry - Riera-Arnau, J.; Ballarín, E.; Llop, R.; Montané, E.; Hereu, P.; Vancells, G.; Padullés-Zamora, N.; Barriocanal, A. M.; Cardona-Peitx, G.; Casasnovas, C.; Montoro, J. B.; Nuñez, M.; et al. (Frontiers in Pharmacology, 2024)
Background The increasing use of non-specific immunoglobulins (NSIGs) and their current shortage show a need for NSIGs’ use prioritization. Data from a clinical perspective are necessary, mainly for pediatric patients. Objectives The aim of the study was to assess the level of clinical evidence (LoE) of the indications that NSIGs are used for, the reasons for discontinuation, and the costs invested. Methods A retrospective multicentric study was conducted on NSIG incident users between September 2019 and December 2021 retrieved from the Registry of Patients and Treatments (RPT) from Catalonia (Spain). LoE was categorized as A) authorized indications, B) unauthorized with scientific support, C) unauthorized without support, and D) unknown (UNK), following local and the United Kingdom’s guidelines as a sensitivity analysis. We also estimated overall spending and costs per patient visit. Results A total of 400 patients were included (17.3% pediatric), with a mean follow-up of 122.1/person-years for adults. The most frequent indications were nervous system and blood diseases. Almost all pediatric patients (56; 81.2%) were treated under A-level indications, as for 217 (65.6%) adults. In the sensitivity analysis, the A-level usage rate decreased to one-third and the B-level usage rate increased by 2–3 times. Furthermore, 37.8% (151) of individuals discontinued. This was predominantly due to remission or no response. The total costs were 868,462.6€/year, with median spending per visit amounting to 1,500€ for adults and 700€ for pediatric patients. Conclusion NSIGs are used in clinical practice mainly for approved indications; however, non-approved indications are still an important issue. This could represent a significant economic burden on the healthcare system, focusing on the pediatric population and those at risk for discontinuation with alternative therapeutic options.